1998
DOI: 10.1183/09031936.98.11010014
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea and diabetes mellitus: the role of cardiovascular autonomic neuropathy

Abstract: Knowledge of conditions associated with an increased prevalence of obstructive sleep apnoea (OSA) may help to identify patients with OSA and might give some insight into the pathogenesis of OSA and its sequelae. A number of earlier, smaller studies hinted at an association between diabetic cardiovascular autonomic neuropathy (AN) and OSA. The present study was, therefore, conducted with the aim of establishing the prevalence of OSA in diabetics with AN and of determining whether OSA is more prevalent in diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 39 publications
2
79
0
5
Order By: Relevance
“…In addition, several smaller studies have looked at whether people with diabetes are more likely to have disordered breathing during sleep. It has been proposed that the autonomic dysfunction that may occur in those with DM could lead to this breathing instability (34)(35)(36)(37)(38). There are not enough subjects in our cohort with diabetes at baseline to have adequate power to examine whether they are more likely to develop SDB or have worsening of their AHI.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, several smaller studies have looked at whether people with diabetes are more likely to have disordered breathing during sleep. It has been proposed that the autonomic dysfunction that may occur in those with DM could lead to this breathing instability (34)(35)(36)(37)(38). There are not enough subjects in our cohort with diabetes at baseline to have adequate power to examine whether they are more likely to develop SDB or have worsening of their AHI.…”
Section: Discussionmentioning
confidence: 73%
“…There are a multitude of factors that influence subsequent glucose concentrations in diabetes patients, including, but not limited to, insulin dosage, carbohydrate and nutritional intake, lifestyle (e.g., sleep-wake cycles and sleep quality, and exercise), and emotional states (e.g., stress, depression, and contentment). [4][5][6][7][8][9][10][11][12][13][14] The effect of these various factors on subsequent glucose levels is not fully understood and may be patient specific or similar across all diabetes patients. In order to optimize control in diabetes patients, there needs to be some method for quantifying or predicting future occurrences of dysglycemia (i.e., high and low blood glucose concentration, also referred to as hyperglycemia and hypoglycemia, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…CAN is often present in subjects with diabetic autonomic neuropathy, which may be often associated with ventilator dysfunction [1]. CAN is associated with increased mortality or adverse cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ficker et al found OSA in 26% of diabetic patients with diabetic autonomic neuropathy [1]. Cardiac autonomic neuropathy (CAN) is commonly observed early in diabetic patients, but most patients are asymptomatic.…”
mentioning
confidence: 99%